Arquitectura en Canarias - Artengo-Menis-Pastrana (1998)
Obra arquitectónica de Felipe Artengo, Fernando Martin y José M. Rodriguez Pastrana
Keywords: ARQUITECTURA; ISLAS CANARIAS; ARTENGO RUFINO, FELIPE; MARTÍN MENIS, FERNANDO; RODRÍGUEZ-PASTRANA MALAGÓN, JOSÉ MA; TENERIFE